2015
DOI: 10.1021/acsnano.5b04950
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Probing of the Dynamics of Sodium Transport and Intercalation-Induced Phase Transformations in MoS2

Abstract: For alkali-metal-ion batteries, probing the dynamic processes of ion transport in electrodes is critical to gain insights into understanding how the electrode functions and thus how we can improve it. Here, by using in situ high-resolution transmission electron microscopy, we probe the dynamics of Na transport in MoS2 nanostructures in real-time and compare the intercalation kinetics with previous lithium insertion. We find that Na intercalation follows the two-phase reaction mechanism, that is, trigonal prism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
145
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(153 citation statements)
references
References 38 publications
(66 reference statements)
8
145
0
Order By: Relevance
“…[52] In-diffusion of Na + ion into the interlayers can fracture the continuous layered structure into a few nanometer-sized domains via formation of high-density defects to relax the strain. Similar to Li-intercalation, the sodium intercalation also triggers a phase transition from 2H-MoS 2 to 1T-NaMoS 2 phases with lattice distortion ( Figure 1F).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[52] In-diffusion of Na + ion into the interlayers can fracture the continuous layered structure into a few nanometer-sized domains via formation of high-density defects to relax the strain. Similar to Li-intercalation, the sodium intercalation also triggers a phase transition from 2H-MoS 2 to 1T-NaMoS 2 phases with lattice distortion ( Figure 1F).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…F,G) Reproduced with permission. [52] Copyright 2015, American Chemical Society. Figure 2C show that the increases in the interlayer distance are 1.88 Å for K-intercalation, 1.01 Å for Na-intercalation, and 0.14 Å for Li-intercalation.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The theoretical specific ion storage capacity for Li-ion batteries (LIBs) and Na-ion batteries (NIBs) can be as high as 2596 mAh g −1 , which is almost one order of magnitude higher than the commercial graphite-based materials (372 mAh g −1 ), holding great promise for future applications ranging from portable electronic devices to large-scale electrical vehicles and power tools. Specifically, a great effort has been devoted to the intercalation of lithium and sodium in a large variety of 2D materials, including graphite, [17,18] borophane, [19] transition metal dichalcogenides, [20][21][22][23] transition metal carbides/carbonitrides, [24,25] and tin-based compounds, [26][27][28] which have larger interlayer spacing bonded by vdW interaction to offer sufficient ionic transport pathway. To bridge up this knowledge gap, we present an in situ investigation on the intercalation of BP with both lithium and sodium ions.…”
mentioning
confidence: 99%
“…The most studied TMDC phases in energy storage application include MoS 2 [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125], MoSe 2 [126][127][128][129][130][131], WS 2 [132][133][134][135], and WSe 2 [136][137][138]. MoS 2 , with the interlayer distance of 6.2 Å, is explored as an anode material for SIBs.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…It was found that the upper plateau at ≈0.85 V corresponds to the intercalation of Na + ions in every other interlayer of MoS 2 , resulting in a formation of Na 0.5 MoS 2 . Before the interlayer space is fully filled, the Na + ions begin to occupy the other spaces between SMo-S layers, generating strain and inducing glide of the sulphur plane along an interlayer atomic plane and phase transition from 2H-to 1T-MoS 2 ( Figure 10(c)-(e)) [109,113].…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%